Chemical modification and characterization of boehmite particles - Brostow, Witold; Datashvili, Tea (Publishing House of Lviv Polytechnic National University, 2008)
Polymerizable organic silane molecules 3-(trimethoxysilyl) propylmethacrylate (3MPS) and vinyltri(2-methoxyethoxy)silane (VTMES) have been introduced onto surfaces of high purity Boehmite (a commercial alumina) via hydroxyl groups on the oxides in order to obtain organic-inorganic hybrid "macromonomers". Changes of surface characteristics have been determined using thermogravimetric analysis (TGA)and Fourier-transform infared spectroscopy (FTIR). The influence of the type of silane used and modification conditions have been etermined. Preheating was applied to some Boehmite samples; it leads to lower concentrations of -OH groups on the powder surface and the adsorption yields lower than in samples without preheating. Modification leads to surface hydrophobicity and thus reduces significantly water below 423K only in un-modified Boehmite. Показано, що полімеризаційноздатні органічні силанові молекули 3-(триметоксисиліл) пропілметакрилату та вінілтри(2-етоксиетокси)силану для одержання органічно-неорганічного гібриду "макромономерів" можуть бути введені на поверхню бемітів високої чистоти (промисловий глинозем) за допомогою гідроксильних груп на оксиди. Зміни у поверхневих характеристиках визначені термогравіметричним аналізом (ТГА) та інфрачервоною спектроскопією з перетворенням Фурьє. Визначено вплив типу силану та умови процесу модифікування. Встановлено, що у попередньо нагрітих зразках спостерігається зменшення концентрації -ОН груп на поверхні і зменшення адсорбційного виходу порівняно із зразками без нагрівання. Модифікація приводить до гідрофобності поверхні, внаслідок чого значно зменшується адсорбція води; за результатами ТГА десорбція води нижче 423К має місце тільки в немодифікованих бемітах.
Хімічна модифікація і характеристика бемітових частин
Keywords: boehmite; macromonomer; silica coupling agent; surface modification; powder filler; беміт; макромономер; кремнеземний агент; модифікація поверхні; порошковий наповнювач